Vibration energy flow in welded connection of plates - Cieślik, J.; Bochniak, W. (Archives of Acoustics, 2006)
The presented results are concerned with energy transmission in two dimensional plate-like structures, which undergo the different frequency force excitation. The method for structural intensity computation is illustrated and formulas of structural intensity for plates and their relationship with internal force and strain are given in works [1–4]. The formulas were used in the program algorithm for structural intensity calculations. The calculations were done with use the FE method to obtain harmonic response solution. Numerical examples are presented – the welded connection of two flat rectangular plates. The model included the force excitation and dampers formed in lines parallel to the one side of plate and the welded connection. The relationship between structural intensity and structural mode shapes as well as the changes of energy flow in plate for the excitation frequency change are discussed.